The Relationship between R&D Collaboration, Subsidies and Patenting Activity: Empirical Evidence from Finland and Germany - Andreas Fier; Bernd Ebersberger; Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This study focuses on the impact of innovation policies and R&D collaboration in Germany and Finland. We consider collaboration and subsidies as heterogeneous treatments, and perform an econometric matching to analyze R&D and patent activity at the firm level. In general, we find that collaboration has positive effects. In Germany, subsidies for individual research do not exhibit a significant impact neither on R&D nor patenting, but the innovative performance could be improved by additional incentives for collaboration. For Finnish companies, public funding is an important source of finance for R&D. Without subsidies, recipients would show less R&D and patenting activity, whilst those firms not receiving subsidies would perform significantly better if they were publicly funded.
Older version: http://hdl.handle.net/10419/24046
Keywords: H50; C14; C25; O38; 330; R&D; Public Subsidies; Collaboration; Policy Evaluation; Forschungskooperation; Forschungssubvention; Innovationspolitik; Wirtschaftspolitische Wirkungsanalyse; Patent; Deutschland; Finnland